The influence of porosity on nanoparticle formation in hierarchical aluminophosphates - Potter, Matthew E.; Riley, Lauren N.; Oakley, Alice E.; Mhembere, Panashe M.; Callison, June; Raja, Robert (Beilstein Journal of Nanotechnology, 2019)
In this work we explore the deposition of gold onto a silicoaluminophosphate, using a variety of known nanoparticle deposition techniques. By comparing the gold particles deposited on a traditional microporous aluminophosphate, with an analogous hierarchical species, containing both micropores and mesopores, we explore the influence of this dual porosity on nanoparticle deposition. We show that the presence of mesopores has limited influence on the nanoparticle properties, but allows the system to maintain porosity after nanoparticle deposition. This will aid diffusion of reagents through the system, allowing continued access to the active sites in hierarchical systems, which offers significant potential in catalytic oxidation/reduction reactions.
Keywords: aluminophosphate; catalysis; hierarchical catalysts; nanoparticles; porosity